Optimization of design and operational parameters of hybrid MED-RO desalination system via modelling, simulation and engineering application - Liyun Wu; Zhong Zheng; Dongming Zhang; Yangang Zhang; Bo Zhang; Zhixin Tang (Results in Engineering)
Based on the current research, the hybridization of desalination technologies has proven to be an effective method of enhancing system performance, minimizing energy consumption, and reducing product water cost. This study focuses on a hybrid MED-RO desalination plant in a large coastal steel enterprise situated in Northeast Asia, China. A comparative analysis of distinct hybrid systems was undertaken, followed by the selection of an optimal process route that aligns with the site-specific conditions and the requirements of downstream freshwater users. To investigate the influences of feed and operational factors on RO process performance, mathematical models were developed for water balance, RO module performance, energy consumption, and economic indicators. Furthermore, according to actual plant conditions, the software simulation and cost benefit analysis were performed for the hybrid desalination system sensitivity analysis and optimization. The outcomes including permeate qualities, concentrate salinity, specific energy consumption, and economic indicators were analyzed to achieve the optimal hybrid system design and operational parameters. Finally, through engineering application of the optimized parameters, the hybrid system performance underwent notable improvement. The calculations reveal that, in comparison to standalone or alternative hybrid systems, this hybrid system exhibits superior energy-saving efficiency, lower operational costs, and reduced carbon emissions. Specifically, the system achieves a recovery rate of approximately 54.22 %, with an average product water cost of 0.5582 US$/m³. Additionally, the energy consumption is 1.015 kgce/m³, translating to an equivalent carbon emission of 2.49 kg/m³.